The Prince of Arab Poets and his Critics: The Battle’s Hidden Motives - Hanene Lahiani, Mohammad Issa Al Hourani, (Opción, 2019)
This paper explains the critical conflicts in the literary circle of Shawqi's time, the different intellectual trends and emancipation movements of the time and the conflict axes and their critical issues via comparative qualitative research methods. As a result, poetry must translate the soul and conscience, without the poet being busy with others, echoing the words of his predecessors and their meanings in his poetry. In conclusion, the critical fight extended to four-time stages that represent in its entirety the reflections of Shawqi's poetry. The most lethal of these stages was after he was crowned as the prince of poets.